FORMULASI DAN EVALUAI STABILITAS FISIK PATCH TRANSDERMAL ALKALOID NIKOTIN DAUN TEMBAKAU (Nicotiana tobacum Linn) DENGAN VARIASI POLIMER DAN ASAM OLEAT - Adi Nurmesa; Nurhabibah Nurhabibah; Aji Najihudin (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2019)
Research on the tobacco leaves nicotine alkaloid (Nicotiana tobacum L) transdermal patch formulation has been carried out as a cigarette dependence therapy with variations in polymers and oleic acid as a penetration enhancer. The purpose of this study is to formulate a stable transdermal patch of nicotine alkaloid tobacco leaf and to see the effect of adding cellulose, PVP and oleic acid to the release of nicotine in vitro. Transdermal patch formulation consists of nicotine alkaloid tobacco leaf, PVP, ethyl cellulose, PVP, PEG 400, propylenglycol and oleic acid. In this study, 3 formulas were made with concentration variants of PVP: EC namely F1 = 1: 1, F2 = 1: 2, and F3 = 1: 3, where the variations in penetration enhancements in the form of oleic acid were F1: 0.10, F2: 0.15, and F3: 0.20. Evaluation of transdermal patch preparations includes organoleptic, matrix weight test, matrix thickness test, drying shrinkage percentage, moisture uptake, matrix fold resistance test, skin irritation test, patch matrix surface pH test, elongation percentage, frezee and thaw test, nicotine content test, and nicotine release (diffusion cell) test, based on physical stability test of all relatively stable transdermal patch formulas and kinetics of transdermal patch release kinetics following first order and the results of statistical analysis using Variant Analysis (ANOVA) showed differences in F1, F2 and F3, and based on the Korsmayer Peppas test following the non-fick law